Optimization and characterization of immobilized e. coli for engineered thermostable xylanase excretion and cell viability - Nor Ashikin, Nur Atiqah Lyana; Siti Fatimah Zaharah, Mohd Fuzi; Shoriya Aruni, Abdul Manaf; Nor Hasmaliana, Abdul Manas; Shalyda, Md Shaarani @ Md Nawi; RosliMd, Illias (Elsevier B.V., 2022)
There are many parameters that may have influenced the properties of cell during immobilization process. Particularly, the immobilization methods, carrier materials, and enzyme loading amount that have been proved to be important for immobilization process. The physiological responses of microorganisms are depending on the immobilization technique used. Typical alterations to the micro-environment of the immobilized cell involved the altered water activity, presence of ionic charges, cell confinement and modified surface tension. In this study, the graphene oxide was selected as a suitable carrier for immobilization process of recombinant E.coli and adsorption was chosen as an appropriate method to improve the production of engineered thermostable xylanase. High level production of thermostable xylanase by immobilized recombinant cell in the 5 L bioreactor was studied by using optimum research surface methodology (RSM) conditions was studied. The immobilization of E. coli onto nanoparticle matrix manages to improve the cell performance by improving the protein expression, reduced the occurrences of cell lysis as well as improved the plasmid stability of the host cell. Thus, immobilization contributes a physical support for both whole cells as well as enzymes to develop a better operative achievement system for industrialized fields and give rise to the biological advancement existing enzyme for instance xylanase.